A novel Ta/W mixed-addendum polyoxometalate with photocatalytic properties. Issue 31 (5th July 2017) - Huang, Peng; Wu, Hai-Yang; Huang, Min; Du, Meng; Qin, Chao; Wang, Xin-Long; Su, Zhong-Min
Abstract : An unprecedented Ta/W mixed-addendum polyoxometalate based on SiTa3 W9 O40 building blocks has been isolated, which exhibits photocatalytic H2 evolution activity. Abstract : An unprecedented polytantalotungstate (POTT), Cs12.5 K4.5 H[Ta12 Si4 W37 O158 ]·25H2 O (1 ), based on the SiW9 Ta3 O40 7− cluster was hydrothermally synthesized. A photocatalytic study revealed that1 exhibits significant photocatalytic water splitting activity.